Perception of Ilonggo college students on sexual aggression. - Arnaldo, Hazel Joy
This study explored the perception of Ilonggo college students on sexual aggression. This was approached with the attempt to generate an Ilonggo youth culture definition and concept of sexual aggression. Four focus group discussions were conducted among varied gender groups (males, females, gays and lesbians). A total of 22 participants between 17-21 years old, from different colleges and universities in Iloilo and were either experienced in dating relationships or not. Results showed that sexual aggression, for these Ilonggo college students, is naturally occuring in dating relationships. There are specific behaviors enacted as sexual aggression in conducive environments, and that coercion is part of the sex play in which one must initiate and the recipient will follow whether he/she likes it or not. There are also gender differences and specific Filipino traits in determining perceived susceptibility to sexual aggression.